PENGARUH BIAYA PRODUKSI TERHADAP LABA USAHA PUDING LAMOTA - Elliza Rizki Wandani; Elisa Juniarti; Hasdita Elies Ramadani; Mia Maelani; Elsa Rahmawati (Jurnal Ekonomi & Bisnis, 2022)
Profit is one measure of the success of the company. The increase in profit is inseparable from the indicators that support it, including production costs. Production costs are the main costs incurred by manufacturing companies to earn revenue and profits. Therefore, the Puding Lamota Business as a manufacturing business needs to examine the effect of production costs on operating profit in several production periods so that it can be used as a reference for production in the following period. The type of data used in this study is quantitative data and is obtained from secondary sources (financial reports and financial documents or notes and receipts) of business units. The data consists of data on production costs and operating profit of Puding Lamota. Data analysis in this study uses a simple linear regression analysis technique where the independent variable is production costs (X) and the dependent variable is operating profit (Y). The results showed that the average operating profit for the three production periods was Rp.1,080,666 and the average production cost was Rp.2,383,333. In addition, this study shows that there is a positive and significant effect of production costs on the operating profit of Puding Lamota.